Response of spatio-temporal changes in sediment phosphorus fractions to vegetation restoration in the degraded river-lake ecotone. (1st September 2022) - Yan, Zhiwei; Wu, Ling; Lv, Tian; Tong, Chao; Gao, Zhongyao; Liu, Yuan; Xing, Bin; Chao, Chuanxin; Li, Yang; Wang, Ligong; Liu, Chunhua; Yu, Dan
Abstract: Phosphorus (P) is an essential element in the ecosystem and the cause of the eutrophication of rivers and lakes. The river-lake ecotone is the ecological buffer zone between rivers and lakes, which can transfer energy and material between terrestrial and aquatic ecosystems. Vegetation restoration of degraded river-lake ecotone can improve the interception capacity of P pollution. However, the effects of different vegetation restoration types on sediment P cycling and its mechanism remain unclear. Therefore, we seasonally measured the P fractions and physicochemical properties of sediments from different restored vegetation (three native species and one invasive species). The results found that vegetation restoration significantly increased the sediment total P and bioavailable P content, which increased the sediment tolerance to P pollution in river-lake ecotone. In addition, the total P content in sediments was highest in summer and autumn, but lower in spring and winter. The total P and bioavailable P contents in surface sediments were the highest. They decreased with increasing depth, suggesting that sediment P assimilation by vegetation restoration and the resulting litter leads to redistribution of P in different seasons and sediment depths. Microbial biomass-P (MBP), total nitrogen (TN), and sediment organic matter (SOM) are the main factors affecting the change of sediment phosphorus fractions. All four plants' maximum biomass and P storage appeared in the autumn. Although the biomass and P storage of the invasive species Alternanthera philoxeroides were lower, the higher bioavailable P content and MBP values of the surface sediments indicated the utilization efficiency of sediment resources. These results suggest that vegetation restoration affects the distribution and circulation of P in river and lake ecosystems, which further enhances the ecological function of the river-lake ecotone and prevents the eutrophication and erosion of water and sediment in the river-lake ecotone. Graphical abstract: Image 1 Highlights: ● Vegetation restoration increases the capacity of sediments to store P. ● Vegetation restoration increased the content and proportion of bioavailable P. ● MBP, TN and SOM are the main factors affecting the change of sediment P fraction. ● Invasive species had greater utilization efficiency of P in surface sediments.